Appraisal on Bangladeshi Medical Didactic approaches, Implementation of Reread Medical Education Curriculum Design, and Suggesting Pharmacology and Therapeutics Discipline throughout the Clinical Years of Graduation epoch. - Haque, Mainul; Mahadeva Rao, U.S (2012)
To assess the medical educational attitudes, and revised education environment in Bangladeshi medical schools. Statistics: Bangladesh has presently twenty-two (22) state-owned medical college and fifty-four (54) private medical colleges. Total 8700 students are admitted each academic year in theses colleges. In government colleges, intake is around 2900 students and in private, around 5800. Survey: Medical education should be always moving like a river otherwise it will not progress to cope with upcoming health challenges. State-owned college’s tuition fees are very meagre amount but in private charges are exorbitant. Both categories are under Public Universities. Suggestion: Right now country is reviewing the national curriculum for medical education. As pharmacology and therapeutics deals with the proper selection of medicine, thus the same should be taught all the clinical years along with internship. Moreover Bangladesh must consider having some modification in the curriculum to have a definite change in long viva-voce system and saving enormous teaching hours. Oral exam should be only for those students’ borderline fail and distinction. Thus to make better prescribers for the country, we must adopt such measures. Conclusion: Thus implementing these measures can ensure to be doctors’ fitness, for practice while adhering to higher standards of care for common Bangladeshi society.